Study of interstage channel of hybrid turbomolecular pump - J. A. Shostak; N. K. Nikulin; P. A. Shostak; G. T. Tsakadze; E. V. Svichkar (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The calculation is based on the use of Monte Carlo method (method of test particle), which consists in the statistical modeling of processes. The article describes an algorithm to construct a mathematical model step by step. The article defines both a probability for gas molecules to pass through the interstage channel of a hybrid turbomolecular pump in forward and backward direction. The effect of the movable walls limiting the channel is taken into account. Results and, accordingly, recommendations, given in the article, can be used in designing a flow passage of the hybrid turbomolecular pumps. The dependencies of a probability for gas molecules to pass through the interstage canal on the relative parameters determining the geometry and dynamics of the channel walls are given